Prediksi Aktivitas Tanpa Masker Dengan Kombinasi Metode Single Exponential Smoothing Dan Fuzzy time series - Edi Suranta Sembiring; Zulfahmi Syahputra (LPPM STMIK Royal Kisaran, 2022)
Abstract: The government has continued to work hard in efforts to prevent the COVID-19 virus with complete vaccines for the community due to the importance of complete vaccination as an aspect of consideration for the implementation of the policy of doing activities without masks. Currently, only 15.91 percent of Indonesia's total population is fully vaccinated. Still a long way from the published figure of 50% of the total population. The goal of this study is to model and predict when the Indonesian government will be able to implement policies that will allow its citizens to move around without wearing masks, assuming that at least 50% of the Indonesian population has received the full dose of the vaccine. As a result, we require calculation guidelines to assist us. Keywords: Mask; SES; FTS. Abstrak: Pemerintah terus bekerja keras dalam upaya pencegahan virus COVID-19 dengan vaksin lengkap bagi masyarakat mengingat pentingnya vaksinasi lengkap sebagai aspek pertimbangan implementasi kebijakan beraktivitas tanpa masker. Saat ini, hanya 15,91 persen dari total penduduk Indonesia yang divaksinasi lengkap. Masih jauh dari angka yang dipublikasikan 50% dari total populasi. Tujuan dari penelitian ini adalah untuk memodelkan dan memprediksi kapan pemerintah Indonesia akan dapat menerapkan kebijakan yang memungkinkan warganya untuk bergerak tanpa memakai masker, dengan asumsi bahwa setidaknya 50% penduduk Indonesia telah menerima vaksin dosis penuh. Akibatnya, kami memerlukan pedoman perhitungan untuk membantu kami. Kata kunci: Masker; SES; FTS